Assessment of food hygiene knowledge and practices among food handlers in selected hotels around uMhlathuze Area - Selepe, Mosa; Mjoka, Joanne (African Journal of Hospitality, Tourism and Leisure, 2018)
The lack of hygiene and safety practices is a major contributor of foodborne outbreaks and it has a great influence on consumers. Each year over two million people die from diarrheal diseases, many of which are acquired from eating contaminated food from food services establishments. The poor personal hygiene of food handlers has been associated with foodborne illness outbreaks. It is important that the issue of hygiene practises and hygiene knowledge is addressed in food service establishments in ensuring that food is safe for consumption. The main aim of the study was to assess the compliance of food handlers towards food hygiene knowledge and behaviours in hotels. The study targeted hotels in uMhlathuze (Empangeni and Richards Bay, South Africa). Nineteen food handlers (head chefs, cooks and supervisors) were interviewed by means of a structured questionnaire. Although the majority of food handlers adhered to basic hygiene principles, there is definitely a need for proper and continuous training in personal and general hygiene, not only for food handlers, but also for management. The results showed that 84.2% of the food handlers have knowledge on hygiene and their hygiene practices were relatively good. However, some errors were observed such as the non-use of disposable gloves when handling or distributing food, tasting food with their hands and usually talking while handling food. The results showed that food handlers still need more training on hygiene on a regular basis so as to avoid those minor mistakes that could become critical in terms of food health and safety.
Articles published in the African Journal of Hospitality, Tourism and Leisure, Volume 7 (4) - (2018)
Keywords: Foodborne; Food handlers; Hygiene knowledge; Hygiene practices; South Africa; Hygiene; Food handling --Safety measures